Coping Style and Quality of Life in Elderly Patients with Vision Disturbances. (21st August 2014) - Oles, Maria; Oles, Piotr
Abstract : Purpose. This study aims at evaluating coping style and quality of life in patients with glaucoma and cataract. Methods. The participants were patients (N = 237, 130F; mean age: M = 67, 8; SD = 9, 5) with low vision caused by cataract ( N = 188 ) and glaucoma ( N = 49 ) who answered the Quality of Life Questionnaire (QOLQ) by Schalock and Keith. The participants were divided by means of cluster analysis ( k -means) according to coping styles measured by CISS (Endler and Parker) into three groups: (1) high mobilization for coping, (2) task-oriented coping, and (3) low mobilization for coping. Results. In all the group, a general quality of life was moderately lowered; however, in task-oriented group it was relatively high. Moreover, task-oriented group had significantly lower level of anxiety (STAI), hopelessness (HS), and loneliness (UCLA LS-R) and higher level of self-esteem (SES) in comparison to the patients from high mobilization and low mobilization for coping. Conclusions. In an old age, adaptive coping with vision disturbances does not necessarily mean flexibility in combining all coping styles, but rather task-oriented coping and an ability to use social support. Extreme mobilization for coping seems not adaptive similarly like low mobilization for coping because it violates balance between environmental requirements and personal resources.